Função de Wigner de dois modos amplificados em um oscilador paramétrico óptico não-degenerado - Hahn, Marcelo Dumas (2009)
The aim of this work is to present the Wigner function of two amplified modes in an nondegenerated optical parametric oscillator which is strictly positive and convergent, characterizing a valid distribution of probability in any regime of operation of the OPO. By doing so it is possible to obtain any statistical value through analytic and numerical calculation, even near threshold, which is impossible with a linearized Wigner distribution. We can verify the presence of squeezing and anti-squeezing in the two modes combined quadratures, and we conclude that this distribution leads to two modes entangled state as well, by the use of the well stablished criterion, which allows for application in quantum information, and more specifically in quantum cryptography. Besides those results, the distribution obtained in this work allows an easy visualization of the probability distribution of the states, bringing some physical insight and has a good stetic appeal.